An Elastic Organic Crystal Enables Macroscopic Photoinduced Crystal Elongation - Chen, Yu-Shan; Wang, Chih-Hsuan; Hu, Yu-Hsuan; Lu, Chun-Yi David; Yang, Jye-Shane (Journal of the American Chemical Society, 2023)
Among the various types of photomechanical deformations of organic crystals, photoinduced elongation of millimeter-scale crystals has yet to be demonstrated. Here we report that the millimeter-sized crystalline rods of an anthracene–pentiptycene hybrid organic π-system (1) are highly elastic and able to elongate up to 21.6% or 0.40 mm without fragmentation upon undergoing [4 + 4] photodimerization reactions. Both the mechanical and photomechanical effects reveal a strong cohesion of the system, even at the interface of 1 and its photodimer 2 and under the conditions of randomized molecular packing, representing a new class of mechanically adaptive organic crystals.